Alteration of the Rhizosphere Microbiota and Growth Performance of Barley Infected with Fusarium graminearum and Screening of an Antagonistic Bacterial Strain (Bacillus amyloliquefaciens) - Yang Fu; Jing Luan; Jialei Shi; Wenzhu Tang; Xianzhen Li; Zhimin Yu; Fan Yang (Microorganisms)
Fusarium graminearum is one of the most important pathogenic fungi with a wide range of plant and animal hosts. This study investigated the effects of F. graminearum infection on the rhizosphere microbiota and growth of two barley (Hordeum vulgare L.) cultivars, Baudin and Kenpi 7, and explored microbiota transplantation as a strategy to enhance disease resistance. By exchanging surface microbiotas between varieties and analyzing rhizosphere bacterial communities using 16S rRNA sequencing, researchers observed that F. graminearum infection increased bacterial diversity and abundance, especially in Baudin barley. Growth indicators (root length, plant height, fresh/dry mass) also exhibited that Baudin barley showed stronger resistance. Functional analysis underscored that the microbial community composition of Baudin barley promoted metabolic pathways related to plant resilience and was associated with improved seedling health. In contrast, Kenpi 7 barley showed weaker resistance, emphasizing the role of seed-specific microbiotas in pathogen defense. An effective antagonistic strain, Bacillus amyloliquefaciens B1, was isolated from Baudin barley, and its inhibition rate against F. graminearum was 80%. The results showed that microbiota transplantation enhanced the disease resistance of low-diversity seeds, and identified B. amyloliquefaciens B1 as a promising biocontrol agent, providing a potential application for sustainable agriculture and reducing dependence on chemical fungicides. This study highlights the importance of seed-associated microbial communities in plant–pathogen interactions and provides a basis for the development of microbiota-based strategies to mitigate crop diseases.